2003
DOI: 10.1177/1532673x02250295
|View full text |Cite
|
Sign up to set email alerts
|

The Sources Of Public Confidence In State Courts

Abstract: Although much is known about public attitudes toward the U.S. Supreme Court, there is very little information about how citizens feel about courts in their own communities. This article hypothesizes that attitudes toward local courts are based primarily on four factors: (a) the actual experiences people have with these courts, (b) the methods by which local judges are selected, (c) the role of the mass media, and (d) various demographic factors. The authors find strong evidence that personal experience matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 22 publications
5
68
1
Order By: Relevance
“…Clawson and Waltenburg (2003) find that the media framing of affirmative-action decisions influences support for the decision among both Blacks and Whites. Examining actual survey data on state courts, Wenzel, Bowler, and Lanoue (2003) find no support for the contention that the media have any effect on diffuse or specific support for community courts. A closer examination of this issue using methods with greater generalizability is thus essential.…”
Section: American Courts and The Mass Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Clawson and Waltenburg (2003) find that the media framing of affirmative-action decisions influences support for the decision among both Blacks and Whites. Examining actual survey data on state courts, Wenzel, Bowler, and Lanoue (2003) find no support for the contention that the media have any effect on diffuse or specific support for community courts. A closer examination of this issue using methods with greater generalizability is thus essential.…”
Section: American Courts and The Mass Mediamentioning
confidence: 99%
“…Few studies have focused on the link between coverage and attitudes within the context of the courts, however, and these studies have either been experimental (Baird and Gangl 2006;Clawson and Waltenburg 2003) or have only examined attitudes toward lower courts (Wenzel, Bowler, and Lanoue 2003), with conflicting results. In an experimental investigation, Baird and Gangl (2006) establish a causal link between the media framing of a Supreme Court decision in legalistic terms and perceptions of fairness in the decision-making process.…”
Section: American Courts and The Mass Mediamentioning
confidence: 99%
“…In these studies, the most consistent finding is that public support is lowest among states with partisan elections (Benesh 2006;Cann and Yates 2008;Jamieson and Hardy 2008;Wenzel, Bowler, and Lanoue 2003). 2 Although these studies provide useful insight, they do not differentiate between states with differing levels of campaign and election activity.…”
Section: Existing Researchmentioning
confidence: 82%
“…9. Previous studies examining public support for state supreme courts have found support for an interaction between an indicator for partisan elections and education (Wenzel, Bowler, and Lanoue 2003) and interactions between political knowledge and indicators for nonpartisan and partisan elections (Cann et al 2008). The survey did not include a direct measure of political knowledge, but court awareness offers a good proxy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation